Acquired Brown's syndrome associated with Hurler-Scheie's syndrome. Issue 4 (April 1989) - Bradbury, J A; Martin, L; Strachan, I M
Abstract : A 5-year-old Caucasian girl with known Hurler-Scheie's syndrome (mucopolysaccharidosis) developed a right Brown's syndrome while under orthoptic review. There was no evidence of trauma or inflammation of the superior oblique tendon, trochlea, or surrounding tissues. The Brown's syndrome in this case may be due to shortening of the superior oblique tendon, associated with the shortening of long tendons of the arms and feet, which is common in Hurler-Scheie's syndrome.